Rhizobacteria as a Potential Microbial Agents for Suppression of Emerging Nematode Diseases in Plants (Global Journal of Agricultural Innovation, Research & Development, 2026)
The increasing limitations and risks associated with synthetic nematicides have intensified interest in rhizobacteria as sustainable alternatives for managing plant-parasitic nematodes. This review synthesizes current advances in understanding rhizobacteria-plant-nematode interactions with a specific focus on mechanistic insights rather than descriptive compilation. It highlights key genera such as Bacillus, Pseudomonas, and Streptomyces, which suppress nematodes through multiple mechanisms including production of nematicidal metabolites, modulation of root exudates, competition in the rhizosphere, and induction of systemic resistance via jasmonic acid and salicylic acid signaling pathways. Particular emphasis is placed on emerging concepts such as rhizobacteria-mediated priming, signaling cross-talk, and interference with nematode host recognition. The review also critically examines current limitations, including inconsistent field performance, gaps in mechanistic understanding, and challenges in formulation and large-scale application. By integrating recent findings and identifying key knowledge gaps, this work provides a clearer conceptual framework and outlines future research directions for developing effective rhizobacteria-based strategies for sustainable nematode management.
Keywords: Rhizobacteria, Biological control, Sustainable agriculture, Plant-parasitic nematodes.